2015
DOI: 10.1515/jce-2015-0010
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with In-hospital Mortality in Patients with Acute Coronary Syndrome

Abstract: Introduction: The recent development of large networks dedicated to ST-segment elevation myocardial infarction (STEMI) led to a significant increase in the number of primary percutaneous interventions (p-PCI) parallel with mortality reduction in Acute Coronary Syndrome (ACS). The number of non ST segment elevation myocardial infarction (NSTEMI) is increasing and the highest mortality rates are encountered in patients with cardiogenic shock and/or out of hospital cardiac arrest associated to ACS. The aim of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…However, increased time from chest pain to revascularization has been proven to represent 1 of the most significant predictors of STEMI-related mortality, 2,3 and STEMI networks for fast reperfusion have been implemented worldwide, demonstrating that a significant reduction in STEMI mortality is achievable via reducing the time from symptoms onset to PCI. 4,5 The fact that the presence of fQRS in this study was associated with a higher mortality, but at the same time did not correlate with one of the most significant predictors of mortality validated so far in the STEMI population (the time from symptoms onset to reperfusion), is a surprising finding. It would be interesting to analyze and discuss this further.…”
mentioning
confidence: 49%
“…However, increased time from chest pain to revascularization has been proven to represent 1 of the most significant predictors of STEMI-related mortality, 2,3 and STEMI networks for fast reperfusion have been implemented worldwide, demonstrating that a significant reduction in STEMI mortality is achievable via reducing the time from symptoms onset to PCI. 4,5 The fact that the presence of fQRS in this study was associated with a higher mortality, but at the same time did not correlate with one of the most significant predictors of mortality validated so far in the STEMI population (the time from symptoms onset to reperfusion), is a surprising finding. It would be interesting to analyze and discuss this further.…”
mentioning
confidence: 49%
“…[22][23][24][25] In patients without ST-segment elevation, as recorded on the post-ROSC electrocardiogram, the decision to perform early PCI can depend on numerous factors. 26 As the specificity and sensitivity of clinical data and biomarkers are less accurate after OHCA, a decision may be extremely difficult to arrive at in such cases. Hemodynamic status, age, duration of CPR or neurological status can all influence the decision of undertaking or postponing coronary angiography.…”
Section: Revascularization In Ohca Patientsmentioning
confidence: 99%
“…At the same time, heart failure is a strong predictor of acute kidney failure in patients with STEMI undergoing primary PCI [4]. Other studies demonstrated the impact of multivessel disease on the outcome of the revascularization procedure, being generally accepted that the presence of a multivessel disease has a negative impact on the survival of ACS patients [5].…”
mentioning
confidence: 99%